Tren topik penulisan artikel ilmiah bidang ilmu perpustakaan dan informasi tahun 2017-2021 menggunakan co – occurance - Rini Arlina; Nining Sudiar; Rosman H (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2022)
This study aims to find out the trending tendencies of topics in the field of Library and Information Science and map the topic from 2017-2021 so that findings can be found in the form of topics that are still few and have the opportunity to be further researched by further researchers. The research topics will be presented using Co-Occurance Vosviewer. The research method used is quantitative descriptive with a search on a URL or a Google Scholar search portal. The results showed that the subjects or keywords found were then standardized using Hawkins Taxonomy. Of the 11 subject classifications of library keywords and information according to Taxonomy Hawkins researchers took the 5 classes with the most use. First, Libraries and Library Service (LIS) is 1447 keyword frequencies with a percentage result of 29%, second information science research (ISR) which is 713 frequencies with a percentage result of 14%, thirdly The Information Professional is 722 frequencies with a percentage of 14%, fourth societal issues (SI) which is 698 frequencies with a percentage result of 14%, and the fifth, Information Technologies (IT) which is 625 frequencies with a percentage result of 12%. It can be concluded that the tendency of the most widely used keywords in research is about "Library" which can be seen in the subject class libraries and library service (LIS).